Influence Cash Ratio, Receivable turn over and Inventory Turn Over to Internal Rate of Return On Operate for Unit Village (KUD) at District Kubung Regency Solok - Oktavian, Deni - (Pendidikan Ekonomi, 2014)
This research intent for menganalisis: (1 ) Influence cash rotation to increase internal rate of return, (2 ) receivable turn over Influence to Increase internal rate of returns, (3 ) inventory turn over Influence to Increase internal rate of returns, (4 ) Cash rotation Influences receivable turn over and Simultans ala inventory turn over to Increase internal rate of returns On Operate for Unit Village (KUD) at district kubung Regency solokObservational type that is utilized in this research is quantitative approaching. Observational object to be done at my district Jazzy regency fella . Data that is utilized is data time series budget period year 2003 2012 one are gotten of on duty Koperindag and UMKM IS examinees Jazzy Regencies be affecting Cash rotation (X1), Receivable turn over (X2), and inventory turn over (X3) as variable independent and Internal Rate Of Return (Y. ) as variable as dependen. That data dianalisis will pass through classic assumption quiz. Meanwhile to test hypothesis was utilized by quiz signifikansi and analisis is bifilar linear regression.Hypthosts testing result partially been gotten that conclusion: (1 ) positive influential Cash rotations and signifikan to Internal Rate Of Returns, seen from signifikans zoom 0,013 littles of points Î± = 0,05 by level affecting 0, 522. (2 ) positive influential receivable turn overs and signifikan to Internal Rate Of Returns, seen from signifikans zoom 0,036 littles of points Î± = 0,05 by level affecting 0,385. (3 ) positive influential inventory turn overs and signifikan to Internal Rate Of Returns, seen from signifikans zoom 0,045 littles of points Î± = 0,05 by affecting as big as 0,367. simultans ala hypthosts testing (4 ) Cash rotations, Receivable turn over, and signifikans ascendant inventory turn over to Internal Rate Of Return, seen from signifikans zoom 0,000 little of point Î± = 0,05. and this research yielding menunjukan that 97,6% internal rate of return variable regarded by free variable which is: Cash rotation (X 1 ), Piutngs rotation (X 2 ) and inventory turn over (X 3 ). Meanwhile its rest 2,4% regarded by innumerable other variable deep observational it.